The Impacts of Saving Habits on the Retirement Savings and Retirement Well-Being - Suzie, Adee (-, 2023)
This research study covers a mixed method with the aim to examine habits that instigate the tendency of society to save and society’s pre-retirement well-being. The issue matter of low personal rates that has been observed and reviewed across the globe over the years have triggered the interest of this research been conducted. Inspired by the aforementioned phenomena, this research is conducted with three (3) main objectives. Firstly, the research attempts to identify the elements that contribute to the generalisation of society’s saving habits, by analysing society’s socio-demographic and behavioural elements that influence their habits to save. Secondly, the research pursues to determine the elements that impact the society’s tendency to save. Thirdly, the research aims to evaluate the elements that impact the pre-retirement well-being that the societies save in, by analysing their happiness, prosperity, good health, comfort and security. The Partial Least Squares Structural Equation Modeling (PLS-SEM) using SMART-PLS is selected to execute the statistical analysis of relationships under the research investigation. The outcome of the research study analysis revealed financial literacy, savings habits, financial risk tolerance, future time perspective, retirement saving and retirement well-being appeared as significant and meaningful (close correlations) and hence supported the decision of the outcomes via the active participation of the research study survey.